Global Economic Prospects and the Developing Countries 2001 - World Bank (Washington, DC, 2013)
Technological innovations and the dismantling of trade barriers over the past decade have contributed to an acceleration of growth in global trade. This acceleration has been associated with faster growth in developing countries as a group. However, many of the poorest countries have not kept pace. This year's report focuses on international trade and discusses policies that are required if developing countries are to benefit from global integration. The report is organized as follows: Chapter 1 examines the prospects for developing countries and world trade and projects that long-term growth has improved and is projected to be higher despite significant vulnerabilities. Chapter 2 analyzes trade policies in the 1990s and discusses reductions in barriers to trade, trends in trade and economic growth, weaknesses in domestic trade-related policies, and trade protection in industrial countries. Chapter 3 explores the relationships between product standards and regulatory barriers to trade, labor standards and trade sanctions, and environmental standards and trade. Finally, Chapter 4 focuses on electronic commerce, the digital divide, and its effects on productivity, international trade, and income distribution, as well as impediments to Internet use, the role of policies, and challenges to regulatory regimes in developing countries.